2007
DOI: 10.1016/j.jacc.2007.06.059
|View full text |Cite
|
Sign up to set email alerts
|

Driving and Implantable Cardioverter-Defibrillator Shocks for Ventricular Arrhythmias

Abstract: Although the risk of ICD shock for VT/VF was transiently increased in the 30-min period after driving, the risk was not elevated during driving and the absolute risk was low. These data provide reassurance that driving by ICD patients should not translate into an important rate of personal or public injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
1
4

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(34 citation statements)
references
References 28 publications
1
28
1
4
Order By: Relevance
“…Peters et al (2004) found a significant association between people having a first MI and being in traffic (car, bicycle, mass transit) an hour before the MI. Similarly, Albert et al (2007) found large associations for having an implantable cardoverter-defibrillator (ICD) shock, specific to ventricular tachycardia or ventricular fibrillation, with driving an hour previously. Both these findings add coherence to other studies finding adverse CVD morbidity or mortality effects associated with vehicular emissions.…”
Section: Health Effects Of Bc Using Epa Criteria For Judging Potentiamentioning
confidence: 99%
“…Peters et al (2004) found a significant association between people having a first MI and being in traffic (car, bicycle, mass transit) an hour before the MI. Similarly, Albert et al (2007) found large associations for having an implantable cardoverter-defibrillator (ICD) shock, specific to ventricular tachycardia or ventricular fibrillation, with driving an hour previously. Both these findings add coherence to other studies finding adverse CVD morbidity or mortality effects associated with vehicular emissions.…”
Section: Health Effects Of Bc Using Epa Criteria For Judging Potentiamentioning
confidence: 99%
“…Risk depends somewhat on specific underlying cardiac arrhythmias. 8 Moreover, the TOVA trial 16 examined the risk of implantable cardioverter-defibrillator (ICD) shocks for VT or ventricular fibrillation (VF) associated with driving. Although the risk of ICD shock for VT/VF was transiently increased in the 30-minute period after driving, the risk was not elevated during driving and the absolute risk was low.…”
Section: Pathophysiologic Features Of Syncope and Drivingmentioning
confidence: 99%
“…As the driving restrictions can make the life situation of the patient and their families more difficult, this may affect adherence to the recommendations. Several studies [52][53][54][55][56][57][58][59][60] point in the direction of low adherence among recipients to the driving ban advised by healthcare professionals. In an early report, despite medical advice never to drive again, Finch et al [45] indicated that 70% resumed driving, with the majority doing so by 8 months after ICD implantation.…”
Section: Psychosocial Adherence and Ethical Issues Of Driving Restrmentioning
confidence: 99%